Hygrothermal performance optimization of lightweight steel-framed wall assemblies in hot–humid regions using orthogonal experimental design and a validated simulation model. (15th May 2023) - Zhan, Qiaosheng; Xiao, Yiqiang; Zhang, Lei; Lin, Zhenghao; Zou, Yukai; Liao, Wei
Abstract: As a layered construction, lightweight steel-framed (LSF) wall assemblies are applicable to different climates and used worldwide. Due to ill-informed construction and material designs, moisture-related durability problems occur, especially in hot–humid areas. Here, a hygrothermal simulation model of typical LSF wall assemblies was validated, and the influences of six construction layers (each with three sets of parameters) on the overall properties and performance were investigated via orthogonal experimental design (OED). Each layer exhibited various impact trends and contribution ratios at different positions. To reduce moisture risks, LSF wall assemblies should generally prevent the infiltration of outdoor moisture as much as possible while strengthening the inward drying capacity. The optimal configuration should comprise multiple water and vapour barriers with a ventilated layer, external insulation, permeable cavity insulation and interior sheathing board with a finish. Finally, this optimization method comprising the hygrothermal simulation and OED techniques could be applied to the hygrothermal performance of LSF wall assemblies under certain climatic conditions. Highlights: Hygrothermal performance of lightweight steel-framed wall assemblies was studied. The simulation model was verified via field measurements in a hot–humid region. The effects of construction and materials were studied by an orthogonal experiment. An optimal lightweight steel-framed wall assembly was proposed for hot–humid areas. Climate adaptive designs of construction and material parameters were generated.